Too secret too long; Great betrayal of Britain's crucial secrets and the cover-up - "Pincher, Chapman" (London, 1984)
A critical analysis of British counter-espionage over the past half century reveals the high-level betrayal of Western security and the subsequent cover-up, detailing the role and failure of secret service, the implications of their operations, and the need for effective regulation of covert activities.
Keywords: Britain's crucial secrets